DNA Microsatellite Markers for Swartzia glazioviana (Fabaceae), a Threatened Species from the Brazilian Atlantic Forest - Spoladore, Janaína; Mansano, Vidal F.; Freitas, Luan C Dias de; Magno Sebbenn, Alexandre; Lemes, Maristerra R. (Applications in Plant Sciences, 2016)
Premise of the study: Development and characterization of a set of DNA microsatellite markers for Swartzia glazioviana (Fabaceae), a naturally rare and threatened tree species, were carried out to investigate its conservation genetics. Methods and Results: Through an enriched genomic library procedure, 10 DNA microsatellite loci were isolated and characterized for the species. The mean expected heterozygosity was 0.776 (0.424-0.894). Cross-species amplifications of these loci were successfully tested for six congener taxa (S. apetala var. apetala. S. flaemingii, S. langsdorffii, S. macrostachya, S. myrtifolia var. elegans, and S. simplex var. continentalis). Conclusions: The 10 polymorphic microsatellite markers developed are quite informative and will provide a valuable resource to study the population and conservation genetics of S. glazioviana and other Swartzia species. © 2016 Spoladore et al. Published by the Botanical Society of America.